Impact evaluation of policies to respond to Covid-19 on Vietnam’s economy - Nguyen, Thi Hoang Oanh (Journal of Finance - Marketing Research, 2023)
This study aims to compare the economic trade-offs in the choice of wholly social isolation and partial social isolation policies by applying the TERM (The Enormous Regional Model) for Vietnam with the assumption of changes in Average Propensity Consumption (APCs) across the country (corresponding to the situation of wholly social isolation) and the change of APC across each region (corresponding to the situation of partial social isolation). After that, the study will compare the results of changes in basic economic indicators in each region according to each APC change scenario of (1) the whole country, (2) the North, (3) the Central, (4) the Southeast, (5) the Mekong Delta. Economic indicators include real GDP and expenditure components of GDP, labor and consumer price index. The study results show that the trade-off of a reduced APC shock across the country is greater than that of a decrease in APC in each region. We can see more clearly that social distancing across the country can have a significantly heavier impact on the economy than social distancing policies by region and locality. The TERM model also shows that APC declines across the country often affect regions where staples are traded domestically rather than those with export strengths.